A Pedagogy of Possibility: Towards Transformative Learning in the Special Collections Classroom - Richardson, Leah; Dugan, Holly (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
Using our work together on an upper-level undergraduate English course as an example, we illustrate that a just combination of librarian and faculty skills and labor, made visible to each other and to students, creates the conditions to enact a transformative student-centered pedagogical approach with special collections as a site of learning and activism. However, we first had to recognize, reflect on, and reject the power dynamics that pervade librarian-faculty collaboration. We will expound on our shared critique of power within the neoliberal corporatized academy that helped us get beyond the conventional librarian-faculty teaching partnership to experiment with critical pedagogies of possibility and enact a feminist praxis; modeling and cultivating interdependent confidence and vulnerability to empower students to be free and creative thinkers.